Unraveling Age-Driven Shifts in Adolescent Cardiorespiratory Fitness: A Comprehensive Analysis Using the Yo-Yo Intermittent Endurance Test - Shahidi, Seyed Houtan; Özsakınç, Burak; Salehi, Amirali (International Journal of Sport Studies for Health, 2024)
Objective: This study aimed to examine cardiorespiratory responses during the Yo-Yo Intermittent Endurance Test in adolescents aged 14–18 years. Methods and Materials: A total of 80 male high school students participated, with 20 from each grade (9–12) at Pendik Vocational and Technical Anatolian High School in Istanbul. Anthropometric measurements, including height and weight, were recorded. Body composition was assessed using a Tanita body impedance analyzer, and aerobic capacity was evaluated using the Yo-Yo IR1 test. Statistical analyses, including ANOVA and Pearson correlation, were performed using SPSS v25. Findings: Significant differences were observed in height, distance covered, and VO2max across age groups. ANOVA revealed significant variations in height and distance covered, with older students performing better. Pearson correlation indicated strong positive relationships between Yo-Yo test levels, VO2max, and distance covered. Conclusion: The findings underscore the need for age-specific fitness assessments in physical education programs to optimize athletic performance during adolescence.